Unlocking the power of swine gut bacteria: newly isolated Blautia strain and its metabolites inhibit the replication of Salmonella Typhimurium in macrophages and alleviate DSS-induced colitis in mice - Jiatong Wei; Yang Liu; Hua Li; Ze Lu; Yanjiao Liu; Yifan Zhang; Cong Lan; Aimin Wu; Jun He; Jingyi Cai; Gang Tian; Daiwen Chen; et al. (Journal of Animal Science and Biotechnology, 2025)
Abstract Background Inflammatory bowel disease is a significant health concern for both humans and large-scale farm animals. In the quest for effective alternatives to antibiotics, next-generation probiotics (NGPs) have emerged as a promising option. The genus Blautia presents a rich source of potential NGP strains. Here we successfully isolated Blautia hominis LYH1 strain from the intestines of healthy weaned piglets and characterized its biological traits. Its anti-inflammatory activity was then assessed using macrophages, while its protective effects against colitis and gut barrier damage were validated in a DSS-induced mouse colitis model. Results B. hominis LYH1 displayed typical characteristics of an obligate anaerobe, including non-hemolytic and non-motile features, and a genome enriched with carbohydrate-active enzyme genes. It produced metabolites with antibiotic-like compounds, demonstrating antimicrobial activity against Escherichia coli. In vitro, B. hominis LYH1 effectively inhibited pathogen replication in macrophages, reducing cellular infections and alleviating inflammatory damage. In vivo, oral administration of B. hominis LYH1 or its metabolites significantly mitigated DSS-induced colitis in mice by suppressing pro-inflammatory cytokines, inhibiting T-lymphocyte activation, and enhancing short-chain fatty acid production. Conclusions Our findings underscore B. hominis LYH1’s potential as a NGP for maintaining gut health and combating intestinal inflammation. These findings offer valuable insights into the development of antibiotic alternatives and innovative strategies for preventing and treating enteritis in both agricultural and medical settings.